A descriptive survey on the design proposals of selected winning entries of a national interior design competition in the Philippines - San Juan, Anna Gabrielle R. author
The study examined and documented select interior design proposals of winning entries in an interior design national competition in the Philippines. A qualitative research method was employed through purposive sampling, specifically non-probability sampling design. Semi-structured interviews with selected judges from the years 2013, 2014, and 2015, and the grand prize winners from 2013 and 2015 were conducted. Note taking, voice recording, and a digital visual aid were used. In addition, winning design entries were analyzed in terms of its originality, universality, and sustainability. It was found that there were specific criteria in each competition year along with a unique design problem. All respondent winners fulfilled the general criteria of originality and sustainability in line with each design problem. One winner was unable to indicate any universal design measures in the design proposal. Similarities in creativity, skill, and competence were found in the cases of the three respondent winners during pre-design stage, in their design considerations, and in the integration of their personal experience and professional practice in the competition entries. Based from this study's results, the design concept, design approach, design appearance, actual project execution, design presentation, and visual impact played significant roles to the respondents' performance in the competition. While originality was seemingly showcased, complete originality was difficult to assume. Visual impact of the design was an important facet, as found from the results of this study. Lastly, inability to fulfill all criteria does not discount an individual's opportunity to gain overall success in the competition because of judges' opinions and interpretations.